The Role of CysC Levels as Biomarkers for Renal Function in the Use of Gentamicin for Preterm Infants Aged 28-36 Weeks with Neonatal Sepsis: A Narrative Literature Review - Ratana, Angelica Devi; Emilda, Emilda; Hendsun, Hendsun (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Premature infants with neonatal sepsis often require antibiotics, such as Gentamicin, commonly used in the NICU to treat suspected Gram-negative infections associated with neonatal sepsis. However, to limit the risk of nephrotoxicity associated with minimum levels, the use of high-dose Gentamicin with extended dosing intervals has been widely adopted in NICU clinical practice. Gentamicin use can impact kidney function. The examination of Cystatin C (CysC) levels as a biomarker to assess kidney function and nephrotoxicity due to antibiotic use is highly recommended, especially in premature infants. Gentamicin use in preterm infants can influence CysC levels as a biomarker for kidney function. The correlation between Gentamicin use, changes in CysC levels, and the impact on kidney function highlights the need for strict monitoring of these parameters. This study concludes that CysC levels can be a crucial indicator in assessing the impact of Gentamicin use on kidney function in preterm infants with neonatal sepsis. Routine monitoring of CysC levels can aid in early identification of potential kidney issues and support appropriate clinical decision-making in the use of antibiotics for this vulnerable preterm infant population.